ANTIBACTERIAL ACTIVITY TEST OF CUCUMBER PEEL EXTRACT (Cucumis sativus L.) AGAINST Streptococcus mutans BACTERIA - Rahmalia Dewi; Masyhudi Masyhudi; Alhawaris Alhawaris; Sinar Yani; Yadi Yadi (FKG ULM, 2024)
Background: Dental caries is a process of tooth demineralization caused by acids produced from food metabolism in bacteria. One of the main etiological factors of dental caries is the microorganisms known as Streptococcus mutans bacteria. S. mutans is one of the components of human dental plaque that is associated with sucrose diet and high caries activity. Cucumber peel extract (Cucumis sativus L.) is known to have an antibacterial activity due to the presence of secondary metabolites such as flavonoids, steroids, alkaloids, saponins and phenols found in cucumber peel. Purpose: This study aimed to determine the antibacterial activity at the lowest concentration of cucumber peel extract (Cucumis sativus L.) against Streptococcus mutans bacteria. Method: This study employed the disc diffusion method with a post-test only control group design. Streptococcus mutans bacteria were cultured on Mueller Hinton Agar media, and cucumber peel extract (Cucumis sativus L.) was applied as the antibacterial agent at concentrations of 0.01 g/ml, 0.05 g/ml, 0.1 g/ml, 0.2 g/ml, 0.4 g/ml and 0.5 g/ml with seven repetitions. Results: The results of the study showed that cucumber peel extract (Cucumis sativus L.) formed inhibition zones around the paper discs against the growth of Streptococcus mutans bacteria at concentrations of 0.4 g/ml and 0.5 g/ml. Conclusion: The concentrations of 0,4 g/ml and 0,5 g/ml are the lowest concentrations of cucumber peel extract (Cucumis sativus L.) that can inhibit the growth of Streptococcus mutans bacteria. Keywords : Antibacterial, Cucumber peel, Dental Caries, Streptococcus mutans